Programa Nacional Escolas Sustentáveis: os impactos do PDDE Escolas Sustentáveis nas práticas de educação ambiental nas escolas estaduais de Mato Grosso do Sul - Siqueira, José Flávio Rodrigues (2022)
This thesis has as object the actions financed, through the Programa Dinheiro Direto na Escola (PDDE) and Escolas Sustentáveis (ES), of the Programa Nacional Escolas Sustentáveis (PNES), in the period between 2014-2019, in the schools of the state education network in the State of Mato Grosso do Sul. The investigation is part of the Research Line and Area of Concentration “Environmental Education” of the Graduate Program in Science Teaching at the Federal University of Mato Grosso do Sul. Such research defends the existence of transformative environmental education activities resulting from the implementation of the Sustainable Schools PDDE in state schools in Mato Grosso do Sul. To this end, we list as a general objective to analyze the Environmental Education actions resulting from the application of financial resources from the PDDE ES for the transformation of schools into sustainable educational spaces in the state education network of the state of Mato Grosso do Sul from the curriculum, the management and physical space according to the PNES. To achieve such objective, we structured the thesis in six chapters: in the first we introduce the theme; in the second, we discuss the available Brazilian academic production regarding sustainable school and/or sustainable educacional spaces in fulfilling the transformation of the school through the dimensions of the curriculum, management and physical space; in the third, we present the national and state documents that propose and promote the operation of sustainable schools and/or sustainable educational spaces, specifically funding through the Sustainable Schools PDDE; in the fourth, we analyze the impact of the PDDE ES on the Organization of Didactic Work, discussing the educational activities contained in the Action Plan and Annex A of schools in the state education network of Mato Grosso do Sul, as well as the items acquired through financial resources; in the fifth, we describe the activities consistent with the principles of Transforming Environmental Education resulting from the application of the financial resources of the Sustainable Schools PDDE, in order to highlight educational practices that proposed local transformations, both socially and environmentally; and in the sixth we weave the final considerations. The theory that guides all the work is the Science of History conceived by Marx and Engels and the central analysis category is the contradiction. Among the results, we have that: the conception of sustainable educational spaces present in the PNES inaugurated in the Mais Educação Program in 2010; the official texts of the PNES reproduce certain neoliberal discourses, especially regarding public-private partnerships, in the expansion of school functions and in the explicit absence of the interference of conflicts and social inequalities in educational quality; there is convergence between the PNES and national environmental legislation, but there is no consolidation of the program and equity in the actions of the management-curriculum-physical space tripod, with activities in the physical space axis predominating; the historical forms of organization of the didactic work suffered alterations with the financed activities, but not in a level that surpassed the Comenian school. The educational activities reported restructure knowledge through dialogue between subjects, respect plurality and cultural diversity and consider the complexity of the environmental issue consistent with the foundations of Transforming Environmental Education by modifying the ways of human relationships in living with other humans, with other beings and with the environment, for providing participatory and democratic moments in the exercise of citizenship and stimulating equitable and solidary social practices.